2021
DOI: 10.1159/000516749
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sildenafil Citrate on Poor Endometrium in Patients Undergoing Frozen-Thawed Embryo Transfer following Resection of Intrauterine Adhesions: A Retrospective Study

Abstract: <b><i>Background:</i></b> The recent studies have shown that sildenafil citrate can enhance estrogen-induced proliferation of the endometrium in infertile women. <b><i>Objective:</i></b> This study was aimed to investigate whether sildenafil citrate could affect pregnancy outcomes in infertile women receiving frozen-thawed embryo transfer (FET) after resection of intrauterine adhesions (IUAs). <b><i>Materials and Methods:</i></b> A total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Regarding the effects of SC on frozen-thawed embryo transfer (FET) cycles in the setting of ART, our results from included studies advocate that SC may positively affect endometrial receptivity, potentially enhancing blood flow to the uterus and improving the implantation rates of embryos during FET ( 19 ) . The medication is thought to exert influence by relaxing uterine smooth muscles and increasing blood flow, which could contribute to a more favorable environment for embryo implantation ( 56 ) . However, research on this topic is ongoing, and while some studies have shown promising results, further investigation is needed to establish the optimal dosage, timing, and overall efficacy of SC in the context of FET cycles ( 57 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the effects of SC on frozen-thawed embryo transfer (FET) cycles in the setting of ART, our results from included studies advocate that SC may positively affect endometrial receptivity, potentially enhancing blood flow to the uterus and improving the implantation rates of embryos during FET ( 19 ) . The medication is thought to exert influence by relaxing uterine smooth muscles and increasing blood flow, which could contribute to a more favorable environment for embryo implantation ( 56 ) . However, research on this topic is ongoing, and while some studies have shown promising results, further investigation is needed to establish the optimal dosage, timing, and overall efficacy of SC in the context of FET cycles ( 57 ) .…”
Section: Discussionmentioning
confidence: 99%
“…12,39 On the other hand, the effect of sildenafil may be differ depending on the cause of thin endometrium. 19 These disorders and underlying factors must be diagnosed and treated before attempting another cycle for achieving fertility.…”
Section: Discussionmentioning
confidence: 99%
“…Common manifestations of IUA include thin endometrium (TE), fibrosis, reduced endometrial receptivity, [ 6 , 7 , 8 , 9 , 10 ] and consequently, a low embryo implantation rate and live birth rate. [ 11 ] Current therapeutic approaches for the treatment of endometrial damage consist of hysteroscopic intrauterine adhesiolysis, [ 12 ] implementation of physical barriers such as intrauterine devices (IUDs) and Foley catheter balloons, [ 13 , 14 ] hormone therapy by exogenous estrogen administration and sildenafil, [ 15 , 16 ] and cell therapy such as colony‐stimulating factor, growth factors, and stem cells. [ 17 , 18 ] However, the clinical use of these strategies remains problematic due to complications such as recurrent postoperative adhesions, notable disparities in hormonal responses, and secondary infections.…”
Section: Introductionmentioning
confidence: 99%